Direct comparison of biomass yields of annual and perennial biofuel crops - Propheter, Jonathan L. (Kansas State University, 2009)
Volatile energy prices, energy independency, and environmental concerns have increased the demand for renewable fuel production in the United States. The current renewable fuel industry in the United States has developed around the conversion of starch into ethanol fuel, supplied mainly by corn (Zea mays L.) grain. Future energy demands cannot be met by corn grain alone; therefore greater amounts of biomass from traditional and alternative crops must be utilized. Nutrient removal by selected biofuel crops is important in order to determine biomass quality, required fertilizer inputs, and economic viability of biofuel cropping systems. The objectives of this study were to evaluate grain, stover, total biomass, and estimated ethanol yields of annual and perennial C4 crops grown under the same soil and weather conditions; and fermentable carbohydrate (FC) yields from extracted sweet sorghum juice. In addition, nitrogen (N), phosphorus (P) and potassium (K) concentrations of biomass were evaluated to determine total nutrient removal for annual and perennial crops. Field trials, at two locations in northeast Kansas, included corn, sorghum [Sorghum bicolor (L.) Moench] and perennial warm-season grass cultivars. Yields and nutrient removal were greater for annual crops than perennial grasses. Annual crop yields varied among cultivars, but were similar between locations and years. Perennial grass yields improved significantly from the 2007 establishment year to 2008, however nutrient removal was not affected by the yield increase. The highest grain yield and grain nutrient removal amounts were observed for corn across both years and locations. Total biomass yields were greatest for sweet and photoperiod sensitive sorghum cultivars. Average extracted sweet sorghum FC yields were 4.8 Mg ha[superscript]1. Estimated ethanol yields of sweet sorghum were greater than all other crop cultivars. Overall, nutrient removal was most affected by biomass yield variation among crop cultivars; however P concentrations, and subsequent removal, were dependent upon soil P levels at individual locations. These results suggest that annual crops can achieve the greatest biomass yields for multiple renewable fuel conversion processes, but are associated with high nutrient removal levels which must be considered when evaluating biofuel energy cropping systems.
Keywords: Biofuel; Annual crops; Perennial grasses; Nutrient removal; Sorghum; Corn; Agriculture, Agronomy (0285)